Plasminogen activator and mouse spermatozoa: urokinase synthesis in the male genital tract and binding of the enzyme to the sperm cell surface (The Rockefeller University Press, 1987)
When ejaculated mouse spermatozoa were embedded in a plasminogen- containing insoluble protein substrate, a zone of proteolysis developed progressively, centered around the sperm head region. Lysis did not occur in absence of plasminogen or in presence of antibodies against the urokinase-type plasminogen activator (u-PA). Zymographic and immunological analyses confirmed the presence of u-PA in extracts of ejaculated mouse spermatozoa. In contrast, the u-PA activity of sperm cells obtained from testis or from vas deferens was low, although these cells were able to bind added murine u-PA. The sites of u-PA synthesis were identified by measuring u-PA activity and u-PA mRNA content in protein extracts and in total RNA preparations of various portions of the male genital tract. The highest levels of u-PA activity and of u-PA mRNA were found in vas deferens and seminal vesicles. The cells that synthesize u-PA were localized by hybridizing frozen sections of various portions of the genital tract to a u-PA cRNA probe. In all tissues examined, u-PA mRNA was predominantly located in the epithelial layer, and the strongest signal was observed over that of the vas deferens. Hence, the u-PA associated with ejaculated sperm cells is probably acquired from genital tract secretions. Sperm-bound u-PA may participate in the proteolytic events that accompany capacitation and fertilization.